Development of an Interactive Mathematics Quiz Game Application Using Unity 2D to Enhance Intelligence and Interest in Calculations - Hutahaean, Marcho Malona; Elsera, Marina; Rahayu, Eka (Cattleya Darmaya Fortuna, 2025)
Games are among the applications popular with the public, as supported by research conducted by MoboMarket. Many games are created merely to entertain students, which partly explains why high school students often lack interest in studying mathematics. Two main factors contribute to this lack of interest: the first is internal, where students have a low curiosity or enjoyment in learning math, and the second is external, where they feel bored and uninterested in doing calculations. This study aims to develop an interactive mathematics quiz game application based on WebGL and developed using Unity 2D as a solution to help change students' perception that mathematics is neither complicated nor difficult. The math quiz game application includes features such as sound effects, back, open, info, quit, and answer buttons. By utilizing Unity 2D technology, this game application is built as a WebGL to allow it to run on a web browser. The development of this math quiz game follows the Game Development Life Cycle (GDLC) method, which is applied in detail. Data collection methods, including questionnaires and surveys, are used to facilitate the game's development process. The game also involves designing a system using UML to model the quiz game, and once the game is complete, an alpha testing method is used to evaluate it. The result of this research is intended as an alternative learning medium for high school students in the form of a game that can be played on a web browser.